Recent advances in different modal imaging-guided photothermal therapy. (November 2016) - Chen, Qiwen; Wen, Jia; Li, Hongjuan; Xu, Yongqian; Liu, Fengyu; Sun, Shiguo
Abstract: Photothermal therapy (PTT) has recently attracted considerable attention owing to its controllable treatment process, high tumour eradication efficiency and minimal side effects on non-cancer cells. PTT can melt cancerous cells by localising tissue hyperthermia induced by internalised therapeutic agents with a high photothermal conversion efficiency under external laser irradiation. Numerous in vitro and in vivo studies have shown the significant potential of PTT to treat tumours in future practical applications. Unfortunately, the lack of visualisation towards agent delivery and internalisation, as well as imaging-guided comprehensive evaluation of therapeutic outcome, limits its further application. Developments in combined photothermal therapeutic nanoplatforms guided by different imaging modalities have compensated for the major drawback of PTT alone, proving PTT to be a promising technique in biomedical applications. In this review, we introduce recent developments in different imaging modalities including single-modal, dual-modal, triple-modal and even multi-modal imaging-guided PTT, together with imaging-guided multi-functional theranostic nanoplatforms.